Association of Kir genes with blood pressure responses to dietary sodium intervention: the GenSalt study. Issue 12 (December 2018) - Gong, Xinyuan; Han, Xikun; Lu, Xiangfeng; Chen, Jing; Huang, Jianfeng; Kelly, Tanika; Chen, Chung-Shiuan; He, Jiang; Gu, Dongfeng; Chen, Shufeng
Abstract Blood pressure (BP) responses to dietary sodium intervention vary among individuals. The inwardly rectifying potassium channel (Kir) is a potassium-selective ion channel that allows potassium ions to move more easily into rather than out of the cell. We aimed to investigate the associations of Kir genes with BP responses to dietary sodium intervention. A 7-day low-sodium intervention followed by a 7-day high-sodium intervention was conducted among 1906 participants. BP measurements were obtained at baseline and during each dietary intervention. Both single-marker and gene-based analyses were performed to explore the associations between Kir gene variants and BP responses to dietary sodium interventions. The genetic risk score (GRS) was used to assess the cumulative effect of the variants on the BP response to the sodium interventions. During the low-sodium intervention, markers rs858009, rs2835904, and rs860795 inKCNJ6 were significantly associated with the systolic BP (SBP) response (P  = 8.82 × 10−6, 3.32 × 10−6, and 2.39 × 10−4, respectively), whereas rs858009 and rs2835904 were significantly correlated with the mean arterial pressure (MAP) response (P  =  1.64 × 10−4 and 2.72 × 10−4, respectively). Marker rs2836023 showed a significant association with the SBP response (P  =  5.72 × 10−5 ) to the high-sodium intervention. The GRS stratified by quartile grouping or as a continuous variable was associated with the BP response to the sodium interventions. Gene-based analyses consistently revealed thatKCNJ6 was significantly associated with the BP response to the sodium interventions. These findings suggest thatKCNJ6 may contribute to variation of BP responses to dietary sodium interventions. Future studies are warranted to confirm these findings and to identify functional variants for salt sensitivity.